1994
DOI: 10.1007/bf02088136
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoduodenal bile transit in cholecystectomized subjects

Abstract: The hepatic hilum-duodenum transit time (HHDT) was evaluated in cholecystectomized subjects to assess its relationship with the motor function of the sphincter of Oddi (SO) and its diagnostic accuracy in the detection of SO dysfunction. The study was performed in asymptomatic controls and symptomatic patients with SO dysfunction before and after sphincterotomy. HHDT showed a direct correlation with manometric SO maximal basal pressure (r = 0.77; P < 0.001) but not with SO phasic activity. In sphincterotomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Although 1 study showed promise for scintigraphic drainage tests in predicting biliary SOD (with a high proportion of patients with dilated biliary trees), 15 this has not been reproduced by others: Darweesch et al, 16 67% sensitivity; Corazziari et al, 17 50% specificity; and Craig et al, 18 25% to 38% sensitivity. It is not surprising that patients with normal-size bile ducts will likely have different drainage determinants and that biliary scintigraphy is not likely to predict pancreatic sphincter abnormalities well.…”
Section: Discussionmentioning
confidence: 95%
“…Although 1 study showed promise for scintigraphic drainage tests in predicting biliary SOD (with a high proportion of patients with dilated biliary trees), 15 this has not been reproduced by others: Darweesch et al, 16 67% sensitivity; Corazziari et al, 17 50% specificity; and Craig et al, 18 25% to 38% sensitivity. It is not surprising that patients with normal-size bile ducts will likely have different drainage determinants and that biliary scintigraphy is not likely to predict pancreatic sphincter abnormalities well.…”
Section: Discussionmentioning
confidence: 95%
“…The mean biliointestinal (bilioduodenal) transit time in patients with PCS in the present study was 12.7 ± 13.3 minutes. Corazziari et al 9 reported a mean biliointestinal (bilioduodenal) transit time of 12.5 ± 2.2 minutes in patients with post cholecystectomy pain and a mean biliointestinal (bilioduodenal) transit time of 6.7 ± 2.6 minutes in asymptomatic controls, thus showing an obvious delay in the PCS patients. The bile duct to the jejunum transit time (mean = 30.1 minutes) was also markedly increased compared with the bile duct to the duodenum transit time (mean = 12.7 minutes) in the patients with PCS.…”
Section: Discussionmentioning
confidence: 99%
“…Los pacientes con disfunción del esfínter de Oddi tipo II y III son de diagnóstico y manejo controvertidos. En nuestra opinión, todo paciente con sospecha de disfunción del esfínter de Oddi tipo II y III debe ser llevado a gammagrafía hepatobiliar pre-CPRE debido a que la especificidad del estudio de medicina nuclear es al menos del 90 % (14,(31)(32)(33)(34). Además, en la evaluación del dolor tipo biliar pos-…”
Section: Fuente De Financiaciónunclassified